Mountain Laurel - Benton, Lori (Thorndike, Maine : Center Point Large Print, 2021)
"North Carolina, 1793 Ian Cameron, a Boston cabinetmaker turned frontier trapper, has come to Mountain Laurel hoping to remake himself yet again-into his planter uncles heir. No matter how uneasily the role of slave owner rests upon his shoulders. Then he meets Seona- beautiful, artistic, and enslaved to his kin. Seona has a secret: shes been drawing for years, ever since that day she picked up a broken slate to sketch a portrait. When Ian catches her at it, he offers her opportunity to let her talent flourish, still secretly, in his cabinetmaking shop. Taking a frightening leap of faith, Seona puts her trust in Ian. A trust that leads to a deeper, more complicated bond. As fascination with Seona turns to love, Ian can no longer be the man others have wished him to be. Though his own heart might prove just as untrustworthy in setting his course, he cannot simply walk away from those his kin enslaves. With more lives than his and Seonas in the balance, the path Ian chooses now will set the course for generations of Camerons to come. A story of choice and consequence, of bondage and freedom, of faith and family"- -
Keywords: Slaves -- Fiction; Plantation owners -- Fiction; Women artists -- Fiction; Interracial dating -- Fiction; Choice (Psychology) -- Fiction; Man-woman relationships -- Fiction; North Carolina -- Social life and customs -- 18th century; Fiction; Christian fiction; Love stories; Historical fiction